Susumaton oral narratives of Leyte - Alunan, Merlie M. (Quezon City Ateneo de Manila University Press, 2016)
"From the Waray word "sumat" for "to tell," the susumaton are oral narratives told by the paragsumat, or storykeepers, either informally during social gatherings or in a more formal fashion in the case of tales of a more formal provenance such as a folklore. The stories are rooted in the country's rich and continuous oral traditions, a treasure trove that includes epics, proverbs, riddles, and songs, among others, all of which predate the arrival of the Spanish in the 16th century. Gathered in Susumaton are 98 of these narratives collected from seven towns in Leyte: Dulag, La Paz, Tolosa, Tanauan, Palo, Barugo, and Carigara. In the book, they are presented as they were told, enabling the reader to echo the storyteller's voice as he reads. English translations are supplied, and an informative introduction by Alunan provides context."--Provided by the publisher.
An mga umurukoy ha Bough Building=The dwarf dwellers of Bough Building Amador Profetana -- Mga umurukoy ha Sabang=Invisible residents of Sabang Florencio Marpa -- Bubon=The dwell Diana Quiña -- Makaharadlok nga Katulangan=The perils of Katulangan Arcadia Acebo -- An lungib ha Bangon=The mysterious cave of Bangon Manuel Ipil -- Urusahon nga dalan tikadto ha Barugo=The mysterious road to Barugo Nena Oyzon -- Dida ha Salangi=A place called Salangi Lucila Lurica -- Hi Domingo Oriogue= A man named Domingo Oriogue Jose Negado, Panfilo Insigne -- An Boholano ha Canumantag=The Boholano who staryed to Canumantag -- An tulay ha Canumantag=The mysterious Canumantag Bridge -- Kardagaw=A man named Kardagaw Eduardo Oyzon -- Sangkay nga engkantohanon=My engkanto friends Flora Buena -- Hi Apoy Merin ug an tawo nga sisihon=Apoy Merin and the barnacled man Fe Apostol Silay -- Kalaghongan=Kalaghongan Isabel Arandia -- Mga higante ha Tolosa=The giants of Tolosa Mike kahano -- An anakan nga naengkanto=A young mother wooed by a fairy man Concepcion Serdeña -- Hi Gimay=A woman named Gimay Matile Marpa -- Higante nga bisita=Visit from a giant Corazon Acebo -- Aswang=Witch Pomposa Musca -- Hi Pedring paradalos=Pedring the weeder
Includes bibliographical references.
In English; with original in Waray.
Keywords: Folklore -- Philippines -- Leyte Island; Legends -- Philippines -- Leyte Island; Tales -- Philippines -- Leyte Island